Underwater ultrasonography and blood sampling provide the first observations of reproductive biology in free-swimming whale sharks ... : يوفر التصوير بالموجات فوق الصوتية تحت الماء وأخذ عينات الدم الملاحظات الأولى للبيولوجيا الإنجابية في أسماك قرش الحوت حرة السباحة ... - Rei Matsumoto; Kiyomi Murakumo; Ryo Nozu; David Acuña-Marrero; JR Green; SJ Pierce; CA Rohner; H Reyes; SM Green; ADM Dove; ML Torres; AR Hearn (OpenAlex, 2023)
We report on a non-invasive technique for observing the reproductive states of wild, free-swimming whale sharks Rhincodon typus for the first time. Female whale sharks (n = 22) were assessed using underwater ultrasonography and a novel blood-sampling technique at Darwin Island in the Galapagos Marine Reserve, Ecuador. Despite the widely held assumption among researchers that the post-pelvic distention of large females is indicative of pregnancy, ultrasound provided no evidence of embryos or egg cases. However, the presence of follicles (diameter: 28.5-83.6 mm) was confirmed in 2 female sharks of 11-12 m total length (TL). Additionally, 3 steroid hormones (estradiol, testosterone, and progesterone) were analyzed in blood plasma from 6 female sharks (11-12 m TL). Hormone levels were similar to, or lower than, those obtained from an immature female in the Okinawa Churaumi Aquarium. Based on these results, we infer that female whale sharks (TL >11 m) in this study were mature but not pregnant. The techniques ... : نقدم تقريرًا عن تقنية غير جراحية لمراقبة الحالات الإنجابية لأسماك قرش الحوت البرية التي تسبح بحرية من نوع Rhincodon لأول مرة. تم تقييم أسماك قرش الحوت الإناث (العدد = 22) باستخدام الموجات فوق الصوتية تحت الماء وتقنية جديدة لأخذ عينات الدم في جزيرة داروين في محمية غالاباغوس البحرية في الإكوادور. على الرغم من الافتراض السائد بين الباحثين بأن انتفاخ ما بعد الحوض للإناث الكبيرات يدل على الحمل، إلا أن الموجات فوق الصوتية لم تقدم أي دليل على وجود أجنة أو حالات بويضات. ومع ذلك، تم تأكيد وجود بصيلات (القطر: 28.5-83.6 مم) في 2 من إناث أسماك القرش بطول إجمالي 11-12 م (TL). بالإضافة إلى ذلك، تم تحليل 3 هرمونات ستيرويد (الاستراديول والتستوستيرون والبروجسترون) في بلازما الدم من 6 إناث من أسماك القرش (11-12 م ليرة تركية). كانت مستويات الهرمونات مماثلة أو أقل من تلك التي تم الحصول عليها من أنثى غير ناضجة في حوض أوكيناوا تشوراومي المائي. بناءً على هذه النتائج، نستنتج أن أسماك قرش الحوت الإناث (TL >11 م) في هذه الدراسة كانت ناضجة ولكنها ليست حاملاً. يمكن استخدام التقنيات المستخدمة هنا لأسماك قرش الحوت بنجاح للحصول على ...